Music in our lives rethinking musical ability, development, and identity - McPherson, Gary.; Davidson, Jane W.; Faulkner, Robert R. (New York ; Oxford : Oxford University Press, 2012)
Why do some children take up music, while others don't? Why do some excel, while others give up? 'Music In Our Lives' takes an innovative approach to answering these questions. It is drawn from a research project that spanned 14 years, and closely followed the lives of over 150 children learning music - with enlightening conclusions.
Description based on online resource; title from PDF title page (viewed on May 15, 2012).
Includes bibliographical references.
Keywords: Music and children -- Longitudinal studies; Musical ability in children -- Longitudinal studies; Music -- Instruction and study -- Longitudinal studies